The Stability of novel energetic materials and associated propellants - Wagstaff, D C. (Department of Environmental and Ordnance Systems, 2010)
A study into the degradation of crystalline Hydrazinium Nitroformate (HNF) in isolation has been carried out alongside studies into HNF / polyNIMMO propellant degradation. The contribution of gas / solid autocatalysis in the degradation of the crystalline phase has been determined to be very low. Studies via GC-MS analysis do suggest that the presence (and eventual release) of the crystal impurity, isopropyl alcohol, is a more significant contributor to the eventual autocatalytic breakdown of the crystal matrix. Investigations into the chemical compatibility of HNF with nitrosated and nitrated derivatives of 2NDPA and pNMA indicated that the reaction of HNF is most rapid with N-NO-2NDPA. This reaction between HNF and N-NO-2NDPA is proposed to be the principal route to rapid propellant degradation in 2NDPA stabilised propellant systems. Analysis of a range of polyNIMMO / HNF propellants has allowed development of a hypothesis for this family of propellant compositions over a range of temperatures. The data has indicated that the degradation of polyNIMMO / HNF propellants is a complex process involving a number of interrelated and interdependent reactions. It appears that a significantly different reaction scheme dominates at 80°C compared to either 60°C or 40°C. The incorporation of a 1% anhydrous sodium sulphite + 1% pNMA mixed stabiliser system has shown promise for use in propellant formulations up to temperature of 80°C. Some level of success in stabilisation has also been achieved using very high levels of pNMA within the propellant formulation.